2023
DOI: 10.1097/opx.0000000000001998
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Burden of Astigmatism: A Systematic Literature Review

Abstract: SIGNIFICANCE This is the first literature review to report the epidemiology, patient burden, and economic burden of astigmatism in the general adult population. The unmet needs of astigmatism patients with coexisting ocular conditions (cataract, glaucoma, dry eye, presbyopia, or macular degeneration) and risks associated with untreated astigmatism are also reviewed and reported. PURPOSE This study aimed to identify, report, and summarize the published literature on epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 125 publications
0
10
0
2
Order By: Relevance
“…This differs from the present study and Fuller and Brown’s study, where previously concussed athletes and those with visual conditions were not excluded [ 25 ]. Such athletes were not excluded in the present study, as visual conditions are common in the general population [ 40 , 41 ], and this study aimed to assess the reliability of this tool for community sports settings. This study also aimed to assess the reliability of the tool in the context of sports where there are documented SRC rates and where the tool is likely to be used.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from the present study and Fuller and Brown’s study, where previously concussed athletes and those with visual conditions were not excluded [ 25 ]. Such athletes were not excluded in the present study, as visual conditions are common in the general population [ 40 , 41 ], and this study aimed to assess the reliability of this tool for community sports settings. This study also aimed to assess the reliability of the tool in the context of sports where there are documented SRC rates and where the tool is likely to be used.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported the benefit of correcting low amounts of astigmatism in comparing distance vision and near visual performance with digital devices or night-time driving performance. [30][31][32][33][34] According to a recent systematic literature review on the epidemiology and burden of astigmatism, 35 uncorrected astigmatism decreases the vision-related quality of life and work productivity, in addition to posing an economic burden on patients. Based on these results, a proactive prescription of toric CLs for eyes with astigmatism is recommended because improved visual performance and more patient satisfaction are expected when astigmatism is corrected properly.…”
Section: Discussionmentioning
confidence: 99%
“…The economic toll on patients has also been documented, incurred through reduced education and employment opportunities and the need for often costly astigmatic correction. Most importantly, there is a significant decrease in health-related quality of life including difficulty with daily activities, driving impairment, and increased risk of falls [ 8 ]. It is estimated that a 1D degree of astigmatism can decrease visual acuity by up to 1.5 lines [ 9 ].…”
Section: Introductionmentioning
confidence: 99%